-3(3p+3)-2(4-8p)-3(9+2p)=0

Simple and best practice solution for -3(3p+3)-2(4-8p)-3(9+2p)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3p+3)-2(4-8p)-3(9+2p)=0 equation:


Simplifying
-3(3p + 3) + -2(4 + -8p) + -3(9 + 2p) = 0

Reorder the terms:
-3(3 + 3p) + -2(4 + -8p) + -3(9 + 2p) = 0
(3 * -3 + 3p * -3) + -2(4 + -8p) + -3(9 + 2p) = 0
(-9 + -9p) + -2(4 + -8p) + -3(9 + 2p) = 0
-9 + -9p + (4 * -2 + -8p * -2) + -3(9 + 2p) = 0
-9 + -9p + (-8 + 16p) + -3(9 + 2p) = 0
-9 + -9p + -8 + 16p + (9 * -3 + 2p * -3) = 0
-9 + -9p + -8 + 16p + (-27 + -6p) = 0

Reorder the terms:
-9 + -8 + -27 + -9p + 16p + -6p = 0

Combine like terms: -9 + -8 = -17
-17 + -27 + -9p + 16p + -6p = 0

Combine like terms: -17 + -27 = -44
-44 + -9p + 16p + -6p = 0

Combine like terms: -9p + 16p = 7p
-44 + 7p + -6p = 0

Combine like terms: 7p + -6p = 1p
-44 + 1p = 0

Solving
-44 + 1p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '44' to each side of the equation.
-44 + 44 + 1p = 0 + 44

Combine like terms: -44 + 44 = 0
0 + 1p = 0 + 44
1p = 0 + 44

Combine like terms: 0 + 44 = 44
1p = 44

Divide each side by '1'.
p = 44

Simplifying
p = 44

See similar equations:

| -6.8+2.6+x=9.2 | | 2x^2-53x+141=0 | | 5(x+4)-16=2(x+3)-2 | | -8(3b+2)+(25b-5)=0 | | 20y^2+4y-7=0 | | 22+5=-3x+15 | | 13r+1=7r+8 | | -8x+9x-21=(-12)-16 | | 2t-6=3t+14 | | -386=14+10x | | -10+y=14 | | 12x-6=5x+15 | | .25+.03x=.37 | | 16+x-(11)=18-(5) | | (x-6)-(x+8)=8x | | 12f=-60 | | 6v^2+90=-48v | | 7.4-y=8.3 | | 12x=-2+8x | | x^3-3x=17.2 | | -28=-2c | | -40x^6-5x^5= | | .3x-.7=.5 | | 0.06*200= | | -7+b=-11 | | -48=12a | | 18d^2-89d=-84 | | 7x+4=11x-12 | | y^2-4x^2=20 | | 3(1.7x+12)=46.2 | | ax+2bx+ay+2by= | | 6-9y=16-3y |

Equations solver categories